Stenting of the upper urinary tract: from bottom, from top, from side... - A. B. Novikov; V. P. Sergeev; D. V. Ergakov; E. A. Galliamov; A. G. Martov (Исследования и практика в медицине)
Internal stenting of the upper urinary tract is a widespread urological surgery. Its frequency in modern practice is high and continues to grow due to the widespread use of endourological, percutaneous, and laparoscopic interventions. The presence of a stent in the patient's body often leads to a decrease in the quality of life due to the occurrence of stent-dependent symptoms, which often requires urgent hospitalization. According to various data, they are registered in at least 80% of patients. The most common stent-dependent symptoms are frequent and / or painful urination, urge to mix (up to imperative), nocturia, pain in the lumbar region, macrohematuria. According to existing data, a fair share of responsibility for the development of these symptoms lies with the distal (vesicular) curl of the internal stent, especially if the technology of its installation is not followed or the length of the drainage is incorrectly selected. The review describes methods for correct installation of internal ureteral stents by transurethral retrograde, antegrade, and laparoscopic approaches, as well as a method for installing and removing mono-pigtail drains. The internal drainage procedure is standard, so the focus is on the nuances and details of this widespread manipulation. The given cohort of patients and the range of surgical interventions indicate a significant experience of the authors in this issue. All illustrations are author's own and taken from the daily workflow. It should be noted that the modern understanding of the process and technological equipment ensure correct stenting when performing any interventions with any access. An adequate choice of installation method and correct positioning of the stent, knowledge of simple details and "secrets" allow not only to restore urodynamics, but also to effectively prevent the development of stent-dependent symptoms, thereby preserving patients quality of life.